Concentration dynamics of polychlorinated biphenyls and organochlorine pesticides in blood of growing Grey heron (Ardea cinerea) chicks in the wild. (1st August 2022) - Valters, Karlis; Olsson, Anders; Viksne, Janis; Rubene, Liga; Bergman, Åke
Abstract: Organochlorine contaminants (OCs) – organochlorine pesticides (OCPs) and industrial products and byproducts – are included in different monitoring programmes and surveys, involving various animal species. Fish-eating birds are suitable indicator species for OCs. Adult birds may be difficult to capture, but chicks can be sampled more easily. Blood of birds is a potentially suitable non-destructive matrix for analysis, as OC levels in blood reflect their concentrations in the body. The study was aimed at investigating how age of fast-growing Grey heron ( Ardea cinerea ) chicks affects contaminant levels in their blood and thus how important is sampling at exact age for biomonitoring purposes. In 1999 on Lake Engure in Latvia whole blood samples of heron chicks were collected at three different time points, with seven and nine days in between the first and second and second and third sampling points, respectively. Twenty-two chicks were sampled at all three times. In total, 102 samples were analysed for 19 polychlorinated biphenyl (PCB) congeners, DDT metabolites – DDE and DDD, hexachlorobenzene (HCB), α-, β-, γ-hexachlorocyclohexane (HCH), and trans -nonachlor. Total PCB concentrations averaged around 2000 ng/g dry extracted matter (EM). DDE was the dominant individual contaminant (ca. 800 ng/g EM), followed by CB-153, -138, and −118. Most of the other analysed OCs were below 100 ng/g EM. No significant (p > 0.05) differences in OC concentrations were found between the three sampling occasions, except for trans -nonachlor. This means that blood can safely be sampled for biomonitoring purposes during the 17 days' time window. The analysed legacy contaminants may serve as model substances for other persistent organic pollutants. Graphical abstract: Image 1 Highlights: Concentrations of polychlorinated biphenyls remained stable in heron chicks' blood over time. Concentrations of organochlorines, except for trans- nonachlor, did not change in heron chicks' blood. Contaminant concentrations between plasma and whole blood samples (n = 5) differed little. The findings are important for sampling birds' blood for biomonitoring purposes.